2013
DOI: 10.1002/ejoc.201301536
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐Phenyl‐ and 2,2‐Diarylpyrrolidines through Stevens Rearrangement Performed on Azetidinium Ions

Abstract: A set of azetidinium ions substituted at the nitrogen atom either by a benzyl group or a benzhydryl group were synthesized to delineate the scope of their ring expansion into 2‐phenyl‐ or 2,2‐diaryl‐pyrrolidines through a Stevens rearrangement. Whereas the regioselectivity of the rearrangement is very high, the diastereoselectivity is low when 2,3‐disubstituted pyrrolidines are produced, except in one case. The major undesirable side‐reaction is a Hofmann elimination leading to ring cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…They unambiguously showed that it involves the formation of the ylide, which is the rate determining step, followed by the concerted rearrangement of the ylide involving a diradical intermediate stabilized within a solvent cage, and the migration with retention of configuration [140]. We also contributed to the knowledge of this reaction, demonstrating its regio-and diastereoselectivity [141][142][143]. Several examples are depicted in Scheme 79.…”
Section: Expansions Into Pyrroles Pyrrolidin-2-ones and Pyrrolidinesmentioning
confidence: 88%
See 1 more Smart Citation
“…They unambiguously showed that it involves the formation of the ylide, which is the rate determining step, followed by the concerted rearrangement of the ylide involving a diradical intermediate stabilized within a solvent cage, and the migration with retention of configuration [140]. We also contributed to the knowledge of this reaction, demonstrating its regio-and diastereoselectivity [141][142][143]. Several examples are depicted in Scheme 79.…”
Section: Expansions Into Pyrroles Pyrrolidin-2-ones and Pyrrolidinesmentioning
confidence: 88%
“…Stevens rearrangement occurs exclusively, with total retention of the migrating carbon (C-3 of the pyrrolidine 321) and high regioselectivity. The second example outlines an efficient entry to 2,2-diarylpyrrolidines 323 recently published [143] based on this reaction with azetidinium such as 322, and the third one outlines the high chemoselectivity that can be reached, since only the primary benzylic (versus secondary) position of the azetidinium ion 324 is deprotonated here.…”
Section: Expansions Into Pyrroles Pyrrolidin-2-ones and Pyrrolidinesmentioning
confidence: 97%
“…The authors were also able to synthesize 2,2-diaryl-pyrrolidines 91 via azetidinium ylides 90 (Scheme 29). [23] Scheme 29. Stevens rearrangement of azetidinium ylides by Couty's group.…”
Section: Eurjocmentioning
confidence: 99%
“…For both the allylation system shown in Scheme A and the arylation system shown in Scheme B, electron‐withdrawing substituents at the 2‐position of the azetidinium ion are required for the observed [2,3]‐rearrangement. In contrast, analogous alkyl‐substituted derivatives were shown to undergo ring‐expansion processes through Stevens rearrangements …”
Section: Azetidine Functionalizationmentioning
confidence: 99%